Smart and Efficient Synthesis of Cyclic Poly(N-isopropylacrylamide)s by Ring Expansion RAFT (RE-RAFT) Polymerization and Analysis of Their Unique Temperature-Responsive Properties - Jin Motoyanagi; Kenichi Bessho; Masahiko Minoda (Molecules)
Cyclic polymers have many interesting properties compared to their linear analogs, but there are very few examples of their synthesis. This is because most cyclic polymers have been synthesized by stepwise processes, including synthesizing homo- or hetero-telechelic end-functionalized precursor polymers and consecutive intramolecularly coupling of both ends of the polymers. This requires a complicated synthesis, and the product yields are very low because the target cyclic polymers are usually synthesized under highly dilute conditions, consequently, making it difficult to systematically analyze the properties of cyclic polymers. In the present research, we have synthesized cyclic polymers using a ring expansion polymerization method. Particularly, the ring expansion RAFT polymerization (RE-RAFT polymerization) that we have developed using a cyclic chain transfer agent is a smart method that can synthesize cyclic polymers very efficiently. In this paper, we successfully synthesized cyclic-poly(N-isopropylacrylamide), which is widely known as a thermo-responsive polymer, by RE-RAFT polymerization. Furthermore, we have compared the thermo-responsive properties of the cyclic-poly(N-isopropylacrylamide)s with those of their linear analogs.